NOP agonist AT-403 promoted sleep in lactic acid-induced acute pain model - Pierce, Bethany E.; McKelvey, Harlie A.; Hite, Mary H.; Lyerly, John M.; Krizan, Ivan M.; Holter, Kimberly M.; Chen, Rong; Zaveri, Nurulain T.; Gould, Robert W. (Frontiers in Pain Research, 2025)
The majority of patients with acute pain experience sleep disturbances that persist despite analgesic treatments such as mu opioid receptor (MOP) agonists and non-steroidal anti-inflammatory drugs (NSAIDs). Further, sleep disturbances increase pain sensitivity, demonstrating a bi-directional relationship between pain and sleep. Given that commonly prescribed MOP agonists disrupt sleep in pain-naïve subjects, it is possible that analgesics exacerbate sleep disturbances associated with pain states. Thus, pain-induced sleep disturbances remain an understudied and undertreated symptom impacting overall quality of life for which development of novel analgesics is critical. Nociceptin/Orphanin FQ opioid receptor (NOP) agonists have shown promise as a novel class of analgesic, and, given sleep-promoting effects in naïve subjects, may improve pain-induced sleep disturbances. We examined the effects of intraperitoneal lactic acid administration, a noxious stimulus which produces acute abdominal pain, on sleep alone and in the presence of analgesics morphine (MOP agonist), meloxicam (NSAID), and novel NOP agonist AT-403. Male and female Sprague Dawley rats were implanted with wireless electroencephalography (EEG) devices to assess sleep duration and brain function using quantitative EEG analyses. Lactic acid dose-dependently decreased rapid eye movement (REM) and non-REM (NREM) sleep duration, and, consistent with prior studies, increased stretching and decreased rearing and grooming behaviors in a concentration-dependent manner. Morphine significantly decreased NREM and REM sleep in pain-naïve states and did not improve sleep following lactic acid administration. Additionally, lower doses of morphine increased high frequency power spectra. In contrast, meloxicam did not affect sleep or quantitative EEG in pain-naïve rats, nor alter lactic-acid induced effects. AT-403 increased NREM sleep duration and slow wave activity during NREM sleep, decreased NREM sleep latency and REM sleep duration both alone and in the presence of lactic acid; at the higher doses tested, AT-403 shifted relative spectral distribution from higher to lower frequency ranges, indicative of a sedative effect. In contrast, AT-403 attenuated lactic acid-induced behaviors and promoted sleep at doses that did not decrease locomotor function. Together, these data demonstrate that current analgesics do not sufficiently alleviate acute pain-induced sleep disturbances whereas NOP agonists represent a novel mechanism for the potential treatment of pain-induced sleep disturbances.